2021
DOI: 10.1021/acs.inorgchem.1c01798
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl(VI) Triflate as Catalyst for the Meerwein–Ponndorf–Verley Reaction

Abstract: Catalytic transformation of oxygenated compounds is challenging in f-element chemistry due to the high oxophilicity of the f-block metals. We report here the first Meerwein−Ponndorf−Verley (MPV) reduction of carbonyl substrates with uranium-based catalysts, in particular from a series of uranyl(VI) compounds where [UO 2 (OTf) 2 ] (1) displays the greatest efficiency (OTf = trifluoromethanesulfonate). [UO 2 (OTf) 2 ] reduces a series of aromatic and aliphatic aldehydes and ketones into their corresponding alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…These studies utilized pristine stock solutions containing only Pu 4+ (aq) or UO 2 2+ (aq) (vs. the Pu/U mixtures described above) and were carried out within the context of UO 2 2+ photochemistry results published previously in HNO 3(aq) . [29][30][31][32][33][34][35] For example, UO 2 2+ (aq) photoreduction to U 4+ (aq) has been shown to proceed with a variety of reductants, including triethylamine, 36 formate, 35 and 2-propanol. 14 We focused this study on 2-propanol, (CH 3 ) 2 CHOH, as a representative sacrificial electron donor (eqn (1) in Scheme 2).…”
Section: +mentioning
confidence: 99%
“…These studies utilized pristine stock solutions containing only Pu 4+ (aq) or UO 2 2+ (aq) (vs. the Pu/U mixtures described above) and were carried out within the context of UO 2 2+ photochemistry results published previously in HNO 3(aq) . [29][30][31][32][33][34][35] For example, UO 2 2+ (aq) photoreduction to U 4+ (aq) has been shown to proceed with a variety of reductants, including triethylamine, 36 formate, 35 and 2-propanol. 14 We focused this study on 2-propanol, (CH 3 ) 2 CHOH, as a representative sacrificial electron donor (eqn (1) in Scheme 2).…”
Section: +mentioning
confidence: 99%
“…The conversion was found to be very low without a base (TOF 1.3 h −1 ) but increased in the presence of a base (TOF 35 h −1 ). 16 Warner et al reported the activity of plutonium( iii ) isopropoxide [Pu(O i Pr) 3 ] to act as a potent catalyst for the above-mentioned reaction, while [Th(O i Pr) 4 ], [U(O i Pr) 3 ] and [U(O i Pr) 4 ] were unexpectedly inactive. 17 Hence, the development of efficient organoactinide catalysts for the transfer hydrogenation of carbonyl compounds with isopropanol under neutral conditions is highly desirable from both synthetic and intellectual points of view.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion was found to be very low without a base (TOF 1.3 h −1 ) but increased in the presence of a base (TOF 35 h −1 ). 16 17 Hence, the development of efficient organoactinide catalysts for the transfer hydrogenation of carbonyl compounds with isopropanol under neutral conditions is highly desirable from both synthetic and intellectual points of view.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic transfer hydrogenation offers an alternative to H 2 for the reduction of C=O compounds 2–5 . Especially, the Meerwein–Ponndorf–Verley (MPV) reduction reaction with alcohols as H‐donors has received more attention 6–10 . The MPV reduction reaction process involves a cyclic six‐membered transition state in which both the alcohol and the C=O are coordinated to the same active center.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Especially, the Meerwein-Ponndorf-Verley (MPV) reduction reaction with alcohols as H-donors has received more attention. [6][7][8][9][10] The MPV reduction reaction process involves a cyclic six-membered transition state in which both the alcohol and the C=O are coordinated to the same active center. This reduction reaction is highly selective for C=O; whereas, other possible reducible bonds, for example, C=C, are retained.…”
Section: Introductionmentioning
confidence: 99%